Safe and Sound: Driver Safety-Aware Vehicle Re-Routing Based on Spatiotemporal Information - Souza, Allan M. de; Braun, Torsten; Botega, Leonardo C. [UNESP]; Villas, Leandro A.; Loureiro, Antonio A. F. (Ieee-inst Electrical Electronics Engineers Inc, 2020)
Vehicular traffic re-routing is key to provide better vehicular mobility. However, considering just traffic-related information to recommend better routes for each vehicle is far from achieving the desired requirements of a good Traffic Management System, which intends to improve not only mobility but also driving experience and safety of drivers and passengers. Context-aware and multi-objective re-routing approaches will play an important role in traffic management. However, most of these approaches are deterministic and can not support the strict requirements of traffic management applications, since many vehicles potentially will take the same route, and, thus, degrade the overall traffic efficiency. In this work, we introduce Safe and Sound (SNS), a non-deterministic multi-objective re-routing approach for improving traffic efficiency and reduce public safety risks (based on criminal events) for drivers and passengers. SNS employs a hybrid architecture and a cooperative re-routing approach for improving system scalability and computation efforts. SNS uses a recurrent neural network to both predict future safety risks dynamics and enable a personalized re-routing in which each vehicle decides the risks it wants to avoid. Simulation results revealed that when compared to state-of-the-art approaches, SNS reduces the CPU time of the re-routing algorithm in approximately 99% and decreases the average safety risk for drivers and passengers in at least 30% while keeping efficient traffic mobility.
Keywords: Safety; Vehicles; Spatiotemporal phenomena; Prediction algorithms; Vehicle dynamics; Heuristic algorithms; Roads; Vehicle routing; vehicle safety; advanced driver assistance